Fundamental of Entrepreneurship ENT300 : Bakery Corporation / Mohd Marzuki Muhammad Izzudin ... [et al.] - Muhammad Izzudin, Mohd Marzuki; Matali, Mohd Syukri; Ho Kok Sunting@Sunting, Dennis Rody; Enche Abdullah, Qistina Asmaa'; Radin Abdul Rahman, Radin Mahathir
Barkery Co. is a business that is actively owned by partnership. The name of this company is actually from the fusion of bar bakery. As the name says,we are trying to introduce a new lifestyle that involves the display of a bar-like premise design and style with the kind of food services and sales that are practiced in a typical bakery house. We would like to emphasize that the bar concept only took its display and atmosphere. Not the food or beverages served there. ln other words,no alcohol will be served.